Consider the equations: f(x) = -6x-1 and g(x)=4x^2

Select the solution for (fg)(x)

1. -6x-1+4x^2

2. -24x^3-4x^2

3. -24x^2-1

4. -24x^5

For (fg (x) plug in the value 4x^2 for each x of f (x)

So f (x) = -6x -1. Plug in here x= 4x^2

You get -6 (4x^2) -1

= -24 x^2 -1

Answer : 3.

I have answered your question.

Niru

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up